Clinical features and outcomes of patients with hepatocellular carcinoma complicated with bile duct invasion - Jihyun An; Kwang Sun Lee; Kang Mo Kim; Do Hyun Park; Sang Soo Lee; Danbi Lee; Ju Hyun Shim; Young-Suk Lim; Han Chu Lee; Young-Hwa Chung; Yung Sang Lee (Clinical and Molecular Hepatology, 2017)
Background/Aims Little is known about the treatment or outcomes of hepatocellular carcinoma (HCC) complicated with bile duct invasion. Methods A total of 247 consecutive HCC patients with bile duct invasion at initial diagnosis were retrospectively included. Results The majority of patients had Barcelona Clinic Liver Cancer (BCLC) stage C HCC (66.8%). Portal vein tumor thrombosis was present in 166 (67.2%) patients. Median survival was 4.1 months. Various modalities of treatment were initially employed including surgical resection (10.9%), repeated transarterial chemoembolization (TACE) (42.5%), and conservative management (42.9%). Among the patients with obstructive jaundice (n=88), successful biliary drainage was associated with better overall survival rate. Among the patients with BCLC stage C, overall survival differed depending on the initial treatment for HCC; surgical resection, TACE, systemic chemotherapy, and conservative management showed overall survival rates of 11.5, 6.0 ,2.4, and 1.6 months, respectively. After adjusting for confounders, surgical resection and repeated TACE were significant prognostic factors for HCC patients with bile duct invasion (hazard ratios 0.47 and 0.39, Ps <0.001, respectively). Conclusions The survival of HCC patients with bile duct invasion at initial diagnosis is generally poor. However, aggressive treatments for HCC such as resection or biliary drainage may be beneficial therapeutic options for patients with preserved liver function.